Genetic variation in resistance to repeated infections with Heligmosomoides polygyrus bakeri, in inbred mouse strains selected for the mouse genome project - Behnke, J.M.; Mugambi, J.M.M.; Clifford, S.; Iraqi, F.A.; Baker, R.L.; Gibson, John P.; Wakelin, D. (Wiley, 2006)
Since the publication of the mouse genome, attention has focused on the strains that were selected for sequencing. In this paper we report the results of experiments that characterized the response to infection with the murine gastrointestinal nematode Heligmosomoides polygyrus of eight new strains (A/J, C57BL/6, C3H, DBA/2, BALB/c, NIH, SJL and 129/J), in addition to the well-characterized CBA (poor responder) and SWR (strong responder) as our controls. We employed the repeated infection protocol (consisting of 7 superimposed doses of 125L3 each administered at weekly intervals, faecal egg counts in weeks 2, 4 and 6 and assessment of worm burdens in week 6) that was used successfully to identify quantitative trait loci for genes involved in resistance to H. polygyrus SWR, SJL and NIH mice performed indistinguishably and are confirmed as strong responder strains to H. polygyrus CBA, C3H and A/J mice all tolerated heavy infections and are assessed as poor responders. In contrast, DBA/2, 129/J and BALB/c mice performed variably between experiments, some tolerating heavy worm burdens comparable to those in poor responders, and some showing evidence of resistance, although only in one experiment with female 129/J females and one with female BALB/c was the pattern and extent of worm loss much like that in SWR mice. Because the genetic relationships between six of the strains exploited in this study are now well-understood, our results should enable analysis through single nucleotide polymorphisms and thereby provide more insight into the role of the genes that control resistance to H. polygyrus.